Long-Term Change of Coastline Length along Selected Coastal Countries of Eurasia and African Continents - Fan Yang; Li Zhang; Bowei Chen; Kaixin Li; Jingjuan Liao; Riffat Mahmood; Mohammad Emran Hasan; M. M. Abdullah Al Mamun; Syed Ahmed Raza; Dewayany Sutrisno (Remote Sensing, 2023)
The acquisition of dynamic coastline change at fine spatial and temporal resolution is essential for enhancing sustainable coastal economic development and coastal environmental conservation. Port construction, land reclamation, urban development, and sediment deposition have resulted in extensive coastline change. In this study, the coastlines along the 56 coastal countries in 1990, 2000, 2010, 2015, and 2020 were delineated and classified into six categories using Landsat time–series images. Five relevant indices, i.e., the length, length ratio, length change rate, index of coastline utilization degree (ICUD), and fractal dimension (FD), were calculated to analyze and explore the spatiotemporal pattern of the coastlines. The results indicate that: (1) The overall length of the coastlines has increased from 3.45 × 105 km to 3.48 × 105 km in the past 30 years, with a net increase of nearly 3904 km. Between 1990 and 2020, the length of the artificial coastline increased by about 13,835 km (4.9~8.8%), while the length of the natural coastline decreased by 9932 km (95.1~91.2%). The increase in artificial coastline is concentrated in Southeast Asia and South Asia. (2) The coastline fractal dimensions (FDs) of countries and continents show that the average FD values of countries in South Asia (1.3~1.4) and Southeast Asia (1.2~1.3) were higher than other countries in the study regions, meaning that the coastlines in South Asia and Southeast Asia are more complex and curved. (3) The value of the ICUD index increased consistently between 1990 and 2015 (177.7~186.6) but decreased sharply between 2015 and 2020 (186.6~162.4), implying that the impact of human activities on the coastline continued to increase until 2015 and began to decrease after 2015. Our study examined the changes in various types of coastlines, which could be significant for sustainable development and environmental protection in coastal areas.